Comparison of plasma and CSF biomarkers across ethnoracial groups in the ADNI. Issue 1 (1st May 2022) - Windon, Charles; Iaccarino, Leonardo; Mundada, Nidhi; Allen, Isabel; Boxer, Adam L.; Byrd, Desiree; Rivera‐Mindt, Monica; Rabinovici, Gil D.; ,
Abstract: Introduction: Ethnoracial differences in cerebrospinal fluid (CSF; amyloid beta 42 [Aβ42], total tau [t‐tau], phosphorylated tau 181 [p‐tau181], and plasma (p‐tau181, neurofilament light [NfL]) biomarkers of Alzheimer's disease (AD) are incompletely understood. Methods: We performed cross‐sectional analyses with and without adjustment for covariates comparing baseline CSF (Aβ42, t‐tau, p‐tau181) and plasma (p‐tau181, NfL) values in 47 African Americans (AAs) matched to 141 non‐Hispanic Whites (NHWs) and 43 Latinos (LAs) matched to 129 NHWs from the Alzheimer's Disease Neuroimaging Initiative (ADNI). Results: Unadjusted comparisons revealed no significant differences in plasma or CSF biomarkers between AAs and NHWs. A trend toward a lower CSF t‐tau and p‐tau181 in LAs compared to NHWs was observed, without significant differences in plasma biomarkers. After adjusting for covariates, there were no significant differences in CSF or plasma biomarkers between AAs and NHWs or between LAs and NHWs. Discussion: Plasma and CSF AD biomarkers may perform similarly across diverse populations but future studies in large, diverse cohorts are needed.